Comparison of Calculated and Experimental Depth Distributions of Gamma Radiation Doses in Polymer Media - Miloichikova, I. A.; Bulavskaya, A. A.; Bushmina, E. A.; Grigorieva, A. A.; Sorokina, A. A.; Stuchebrov, S. G.
The paper discusses a comparison of depth distributions of doses in plastics obtained by simulation in the PCLab software and experimentally with a Theratron Equinox–80 gamma–therapy unit. We used items made of ABS, HIPS and PLA plastics suitable for 3D printing and with different fill factors. Our study has demonstrated that the simulation results are consistent with the experimental ones within the uncertainty limits.
Keywords: Physics